Rethinking urban streetscape: Enhancing urban design qualities for higher walkability at intersection of Itahari, Nepal - Bk, Aasish; Bajracharya, Ashim Ratna (Journal of Innovations in Engineering Education, 2025)
The state of Itahari Chowk currently presents the challenges stemming from urban development, prioritizing vehicular traffic. This article aims to assess the qualitative aspects of physical surroundings, aiming to identify how different urban design features affect walkability. By applying evidence-based design principles within a knowledge-driven framework, the research seeks to study the ways to enhance walkability and propose effective design solutions for pedestrian-friendly environments. The methodology included a detailed site inventory, community perception analysis, and the application of the Serial Vision Method, both before and after the proposed design interventions. The proposed design interventions led to notable improvements in walkability across all observation spots. These findings highlight the potential of thoughtful streetscape design to improve pedestrian experiences. The study offers valuable insights for architects, urban planners, and academics aiming to promote walkability in emerging urban streets.